PENGUASAAN KATA SANDANG BAHASA JERMAN SISWA SMA NEGERI 3 SINJAI DALAM MENYUSUN KALIMAT SEDERHANA - Mirwan, Mirwan; R., Mantasiah; Saud, Syukur (Universitas Negeri Makassar, 2020)
Abstract. This study aims to determine the data and information about the level of mastery of article of German in composing simple sentences and the factors that influence the mastery of German clothing in Sinjai 3 High School students in compiling simple sentences. This research is quantitative descriptive. To collect data used a written test, and a closed questionnaire. Then the data collected was analyzed using percentage techniques. The population in this study were all students of class XI IPS SMA Negeri 3 Sinjai. The sample used in this study was total sampling consisting of 3 classes with 83 students. The results of the study showed that the mastery of German language clothing for Sinjai 3 High School students in compiling simple sentences was in the Less category (58.34%).